THE EFFECT OF LEARNING MODELS (TPS, TPSq, CONVENSIONAL) AND STUDENTS' TAHSIN ABILITY ON PAI LEARNING OUTCOMES - Fitriani Fitriani; Ahsanur Rifqi; Muflihah Muflihah; Rahayu Kariadinata; Adam Malik (Universitas Pakuan, 2023)
The cooperative learning model can be supported in the PAI learning process. This study analyzed the effect of learning models (TPS, TPSq, and Conventional) and students' abilities on Islamic education learning outcomes. This research method uses a quantitative type, with the Nonequivalent Posttest_Only Control Group design, with statistical test analysis using Two Way Anova. The results of the analysis of this study indicate that there are differences in learning models (TPS, TPSq, and Conventional) and students' Tahsin abilities in PAI learning outcomes; it can be seen from the output rank that the TPS learning model is 17.65 less than the mean rank of students in the class model. Learning TPSq is 31.35 (17.65 31.35). The mean rank value of students in the TPSq learning model class is 32.35, more significant than that of students in the conventional learning model class, which is 16.65 (32.35 16.65). The mean rank value of students in the TPS learning model class is 26.96, more significant than that of students in the Conv learning model class, which is 22.04 (26.96 22.04). There are differences in Islamic education learning outcomes for class VII A and B students based on Tahsin’s ability; based on the Statistical Test results, the Sig.2-tailed is 0.000, which is more minor () than 0.05. There are differences in the learning outcomes of students in classes VII B and C based on Tahsin’s abilities; based on the results of the Test Statistics, the value of Sig.2-tailed is 0.006, this value is more minor ( ) than 0.05, and there are differences in the learning outcomes of students in class VII A and C. based on Tahsin ability, based on the results of the Statistical Test the value of Sig.2-tailed is 0.000 this value is more minor () than 0.05.